Genetics in Anorexia Nervosa: where we stand and where we are headed - Mariana Oliveira Ramos de Castro (2021)
Anorexia Nervosa (AN) is a complex and multifactorial eating disorder, which affects the patient's quality of life, with consequences exceeding physiological and mental issues which can ultimately lead to one's death. Despite its urgency, effective treatment is missing, alongside the still insufficient knowledge of AN's etiology. However, it is acknowledged that the field of genetics is involved. Consequently, it is crucial to understand it better, in the hope of improving its management and treatment. Accordingly, this study aims to overview the main approaches to unravel the genetics underlying AN and to discuss the current and future developments in this field. AN is a familial and polygenic illness, which emerges when the combination of genetics and environment favors its development. Although no significant AN genes identified in studies have been definitively confirmed by consistent replications, many Single-Nucleotide Polymorphisms (SNPs) are being studied. Additionally, AN seems to be involved with other traits and disorders (i.e. schizophrenia), and there is promising evidence to consider it a metabolic disease. Considering its encouraging results thus far, additional studies of Genetics in AN are needed to achieve further meaningful findings, which will hopefully contribute to a turnaround in the clinical practice and in the patient's lives.